The Occurrence of 3-Hydroxy-3-methylglutaryl CoA Reductase (NADPH) in the latex of regularly-tapped Hevea brasiliensis - Sipat, Abdullah (1982)
The enzyme 3-hydroxy-3-methylglutaryl CoA reductase (NADPH) from the latex of mature trees of Hevea brasiliensis was studied. It was found to be mainly associated with the bottom fraction of centrifuged latex (42,000 g), although appreciable activity was also detected in the Frey-Wyssling zone. The bottom fraction enzyme has a specific requirement for NADPH as the cofactor and its pH optimum was 6.6 - 6.9 in 0.1 M phosphate buffer. The Arrhenius plot of the enzyme was linear within the temperature range of 12 - 40°C and the Arrhenius activation energy was estimated to be 57.3 kJ/mol (13.7 kcal/mol). The enzyme was very unstable when the latex was collected and centrifuged at ambient temperature. A 30% loss of activity also occurred when the bottom fraction was stored at -15° C for 24 hr. Pre-incubation of the enzyme at 30°C for up to 1 hr resulted in a 90% loss of activity and this was not prevented by washing the bottom fraction or by the addition of either bovine serum albumin (1 %, w/v) or NADPH (2 mM) or dithiothreitol (10 mM) to the assay mixture. Enzyme activity in the washed bottom fraction was saturated at 300 11M R&-HMG CoA and the K m and Vmax were 56 11M and 6.10 pkat/mg protein respectively.